Cognitive-Emotional and Inhibitory Deficits as a Window to Moral Decision-Making Difficulties Related to Exposure to Violence - Zucchelli, Micaela Maria; Ugazio, Giuseppe (Frontiers in Psychology, 2019)
In the present review we illustrate how exposure to violence results in an increased probability of developing functional impairments of decision mechanisms necessary for moral behavior. We focus in particular on the detrimental effects of exposure to violence on emotional (e.g. Empathy), cognitive (e.g. Theory of Mind), and inhibitory control abilities. Relying on studies that document impaired moral behavior in individuals with deficits in these abilities, we propose a “model” of how exposure to violence can affect moral behavior. We then discuss how impaired moral decision making can also be a factor increasing the likelihood of reiterating violence: agents who lack abilities such as understanding and resonating with others’ emotions or inhibitory control, can lead to an increase of violent displays. Thus, if not properly addressed, the noxious effects of exposure to violence on morality can lead to a violence generating cycle. We conclude proposing that interventions targeted at improving moral behavior can maximize their efficacy focusing on mitigating the impact of violence on the basic cognitive, emotional, and inhibitory abilities discussed.